Experimental Research of the Dual-source Evaporator Under Spraying Condition. (2017) - Zhang, Tianjiao; Zhang, Jili; Ma, Liangdong
Abstract: In this paper, a heat pump hot water unit with the dual-source evaporator using air or water as the heat source is proposed. The idea is firstly to use the heat from the bath wastewater to heat the domestic hot water. If the stored wastewater is insufficient, the ambient air will be applied for assisting the heat pump. The structure of the dual-source evaporator is simpler and compacter compared with the traditional form of two evaporators arranged in parallel. For testing it, the heat pump hot water unit with the evaporator is established. The performance of the unit and the dual-source evaporator are investigated experimentally when the bath wastewater is used as the heat source. Experimental results show that the coefficient of performance (COP) of the heat pump can reach 5.02 when the wastewater temperature is 32℃, and the heat transfer coefficient of the evaporator can reach to 1003.56 W/m 2 K. And the temperature of wastewater can be decreased to 8℃ by cyclical utilization. So the effect of heat recovery is remarkable for the heat pump hot water unit with the dual-source evaporator. When air is used as the only heat source, the performance of the heat pump is about the same as that of a conventional air-source heat pump, and this paper does not research on it.